Computational micromechanics of the transverse and shear behavior of unidirectional fiber reinforced polymers including environmental effects. (January 2017) - Naya, F.; González, C.; Lopes, C.S.; Van der Veen, S.; Pons, F.
Abstract: Qualification of Fiber Reinforced Polymer materials (FRP's) for manufacturing of structural components in the aerospace industry is usually associated with extensive and costly experimental campaigns. The burden of testing is immense and materials should be characterized under different loading states (tension, compression, shear) and environmental conditions (temperature, humidity) to probe their structural integrity during service life. Recent developments in multiscale simulation, together with increased computational power and improvements in modeling tools, can be used to alleviate this scenario. In this work, high-fidelity simulations of the material behavior at the micro level are used to predict ply properties and ascertain the effect of ply constituents and microstructure on the homogenized ply behavior. This approach relies on the numerical analysis of representative volume elements equipped with physical models of the ply constituents. Its main feature is the ability to provide fast predictions of ply stiffness and strength properties for different environmental conditions of temperature and humidity, in agreement with the experimental results, showing the potential to reduce the time and costs required for material screening and characterization.